Titanite petrochronology of the Pamir gneiss domes: Implications for middle to deep crust exhumation and titanite closure to Pb and Zr diffusion. Issue 4 (28th April 2015) - Stearns, M. A.; Hacker, B. R.; Ratschbacher, L.; Rutte, D.; Kylander‐Clark, A. R. C.
Abstract The Pamir Plateau, a result of the India‐Asia collision, contains extensive exposures of Cenozoic middle to lower crust in domes exhumed by north‐south crustal extension. Titanite grains from 60 igneous and metamorphic rocks were investigated with U‐Pb + trace element petrochronology (including Zr thermometry) to constrain the timing and temperatures of crustal thickening and exhumation. Titanite from the Pamir domes records thickening from 44 to 25 Ma. Retrograde titanite from the Yazgulem, Sarez, and Muskol‐Shatput domes records a transition from thickening to exhumation at 20–16 Ma, whereas titanite from the Shakhadara dome records prolonged exhumation from 20 to 8 Ma. The synchronous onset of exhumation may have been initiated by breakoff of the Indian slab and possible convective removal of the Asian lower crust and/or mantle lithosphere. The prolonged exhumation of the Shakhdara and Muztaghata‐Kongur Shan domes may have been driven by continued rollback of the Asian lithosphere concurrent with shortening and northwestward translation of the Pamir Plateau.